Cortometraje Sobre juventud digital, Nuevas tendencias de comunicación y relación Entre Personas - Miranda Salazar, Pablo Esteban (2014)
The world has witnessed many technological advances necessary for any field, and in this case Internet has been one of the most attractive and innovative discoveries we have seen. Communication is returned much more efficient, appealing and interactive which has generated a number of graphic elements that reflect a feeling, a thought or a feeling, making young people today adopt new trends of communication and relationship between people, we give an example to Facebook which has been the revolution of social networking, today you can post that over 50 percent of the world has a profile, while maintaining contact with people all over the planet. If we add to this beautiful video media calls that makes it much interesting allowing us to observe the other person at the right time and in real time, which is a gigantic advance communication. Skype is a company leader in video calls that is why with this film we can see the use of these benefits it has brought us... See the attached file